2016
DOI: 10.1159/000441885
|View full text |Cite
|
Sign up to set email alerts
|

Critical Dietary Habits in Early Childhood: Principles and Practice

Abstract: The adequacy of a diet is usually evaluated based on nutrient intake. As people eat foods but not nutrients, food-based dietary guidelines (FBDG) are needed. To evaluate dietary habits in infants and young children, the following stepwise approach is suggested: (1) develop country-specific FBDG to identify the potential of common nonfortified foods to ensure adequate nutrient intake and (2) examine potential 'critical' dietary patterns if main food groups are excluded, such as in vegetarian diets or if a famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The importance of consuming red meat is extremely clear for health and especially for children's development. However, the consumption habits of young individuals in the family will affect their health throughout their entire lives (46)(47)(48)(49) . All consumers should be informed about the importance of avoiding an unbalanced diet and instead aiming for healthy and balanced nutrition, and also be informed of the importance of the nourishing natural products in all food items, not just red meat.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of consuming red meat is extremely clear for health and especially for children's development. However, the consumption habits of young individuals in the family will affect their health throughout their entire lives (46)(47)(48)(49) . All consumers should be informed about the importance of avoiding an unbalanced diet and instead aiming for healthy and balanced nutrition, and also be informed of the importance of the nourishing natural products in all food items, not just red meat.…”
Section: Discussionmentioning
confidence: 99%
“…HELENA study 1 Balanced diet (FKE) 2 Meat, processed meat (g/day) Table 1. Comparison of the eating habits of adolescents (HELENA study) with the FKE (Research Institute for Child Nutrition) recommendations for an age-appropriate balanced diet [1,3]. ( 1 Age group: 12.5 to 17.5 years; 2 Age group: 13 to 14 years.…”
Section: Foodmentioning
confidence: 99%
“…to WHO, VAD is predominantly associated with malnutrition and remains a leading cause of blindness in school going children [28]. Selective dietary patterns, climate and sociocultural factors are other variables leading to VAD [29]. Statistical data showed that girls having carbohydrates and lipids as primary diet were more exposed to VAD, comprising 79.4% and 12.17%, respectively (Table 4).…”
Section: Accordingmentioning
confidence: 99%